Additional Diagnostic Yield of the Rapid Drink Challenge in Chicago Classification Version 4.0 Compared With Version 3.0 - Wang, Hoyoung; Jung, Kee Wook; Noh, Jin Hee; Ahn, Ji Yong; Lee, Jeong Hoon; Kim, Do Hoon; Choi, Kee Don; Song, Ho June; Lee, Gin Hyug; Jung, Hwoon-Yong (Journal of neurogastroenterology and motility, 2024)
Chicago classification version 4.0 enhances the diagnosis of esophageal motility disorders using position change and provocative tests such as multiple rapid swallows and a rapid drink challenge. This study investigates the diagnostic role of the rapid drink challenge based on Chicago classification 4.0 using a functional luminal imaging probe to estimate the cutoff value. This study included 570 patients who underwent esophageal manometry with a rapid drink challenge between January 2019 and October 2022. The diagnostic flow was analyzed according to Chicago classification 4.0. Ninety-nine patients (38, achalasia; 11, esophagogastric junction outflow obstruction; 7, ineffective esophageal motility; 1, hypercontractile esophagus; and 42, normal esophageal function) failed the rapid drink challenge. Among the 453 participants, 50 and 86 were diagnosed with achalasia and esophagogastric junction outflow obstruction, respectively, using Chicago classification 4.0. In 249/453 (55.0%) patients initially diagnosed with esophagogastric junction outflow obstruction using Chicago classification 3.0, the diagnosis was changed to achalasia (n = 28), hypercontractile esophagus (n = 7), ineffective esophageal motility (n = 7), or normal esophageal function (n = 121) using Chicago classification 4.0. Rapid drink challenge-integrated relaxation pressure's diagnostic cutoff value was 19 mmHg. Nine patients had diagnoses changed after the rapid drink challenge, including 3 with panesophageal pressurization. Chicago classification 4.0 increased the diagnostic yield of the rapid drink challenge by 2.0% (9/453 patients). However, the rapid drink challenge had a failure rate of 17.9% (99/552 patients). Given the relatively low diagnostic yield and high failure rate of the rapid drink challenge, we recommend adopting an individualized approach to manometry.